O ensino da música no município de Palmas, após o advento da Lei 11.769/2008 - MARTINS, Adriana dos Reis (2011)
The interest in researching the way the teaching of music was being carried out in the city of Palmas started when the city educational bureau introduced a distinguished proposal of education, different from the other Brazilian cities, in the year 2005. The project was named Salas Integradas and the aim was to offer the teaching of music to the students of the city schools. It started before the approval of the Law 11.769/2008, which states that the teaching of music in the basic education had to be mandatory. In these circumstances, it was verified the need of researching the strategies used by the City Educational Secretariat when planning on including the teaching of music in the city schools as well as the outlining of the profile of the educational professional in charge of the music classes in the city schools which offer full-time education. The research has a qualitative approach, theorectically based on the complex thoughts of Morin and also on works in the area of Education, Music Education and Laws. The field research was carried out in two city schools and two groups of music teachers. On the final considerations the public policies taken into account for the effectuation of the teaching of music were analyzed and also the profile of the education professional working in that teaching.